2021
DOI: 10.17559/tv-20200408160557
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology Proposal for Selecting the Optimal Location for Small Hydropower Plants

Abstract: The hydropower potential in the Republic of Serbia, as the most important renewable energy source, has been estimated at around 17000 GW•h per year, where approximately 2000 GW•h could be obtained from small hydropower plants (SHP). Small hydropower plants in Serbia currently produce 150 GW•h. Accordingly, the share of the electricity production from small hydropower plants in the total electricity production in Serbia is too small. The paper presents a model for the selection of optimal locations for small hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…GIS analyses are very helpful in choosing the location, which significantly accelerates the work, as stated in Odiji et al [19], Othman et al [20], Al-Juboori and Guven [21], and Bezabih [22]. These analyses have already been used to search for potential locations for hydropower plants around the world, e.g., in Thailand [23], Korea [24], South Africa [25], Iran [26], Italy [27,28], Turkey [29], Ireland [30], India [31,32], Brazil [11] and in the United States [33,34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GIS analyses are very helpful in choosing the location, which significantly accelerates the work, as stated in Odiji et al [19], Othman et al [20], Al-Juboori and Guven [21], and Bezabih [22]. These analyses have already been used to search for potential locations for hydropower plants around the world, e.g., in Thailand [23], Korea [24], South Africa [25], Iran [26], Italy [27,28], Turkey [29], Ireland [30], India [31,32], Brazil [11] and in the United States [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…When choosing sites for small hydropower plants, multiple factors should be taken into account, including environmental (ecological) [28,41,42], economic [18,28,43], social [23,41], topographic [5,[43][44][45][46][47], geological [13,48], technical [41,49], hydrological [5,[45][46][47] and legal (administrative) ones [50,51]. The literature review carried out for the purposes of this study revealed that, in different parts of the world, different criteria are used to select a location for a hydropower plant.…”
Section: Introductionmentioning
confidence: 99%